2008
DOI: 10.1103/physrevb.77.115412
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of mercury adsorption on metal surfaces

Abstract: Density functional theory ͑DFT͒ calculations are used to characterize the interaction of mercury with copper, nickel, palladium, platinum, silver, and gold surfaces. Mercury binds relatively strongly to all the metal surfaces studied, with binding energies up to ϳ1 eV for Pt and Pd. DFT calculations underestimate the energy of adsorption with respect to available experimental data. Plane-wave DFT results using the local density approximation and the Perdew-Wang 1991 and Perdew-Burke-Ernzerhof parametrizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 61 publications
8
49
0
Order By: Relevance
“…A decrease in the adsorbateinduced work function indicates the electropositive behavior of Hg, which is consistent with the previous work of Steckel. 6 To understand the impact of Hg on Pd alloys and overlays, the local density of states (L-DOS) of surface atoms was examined. Overall, the L-DOS corresponding to the different surfaces with the stronger Hg interactions, such as Pd/Au(111), 2Pd/Ag(111), and Pd 3 Cu(111), is studied and compared with pure Pd(111).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the adsorbateinduced work function indicates the electropositive behavior of Hg, which is consistent with the previous work of Steckel. 6 To understand the impact of Hg on Pd alloys and overlays, the local density of states (L-DOS) of surface atoms was examined. Overall, the L-DOS corresponding to the different surfaces with the stronger Hg interactions, such as Pd/Au(111), 2Pd/Ag(111), and Pd 3 Cu(111), is studied and compared with pure Pd(111).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] In particular, Pd sorbents showed enhanced Hg removal capacity at high temperatures. 4 There are numerous experimental 4,5,[8][9][10][11][12][13][14][15] and theoretical 6,7,16 studies for Hg adsorption on metal surfaces. Additionally, many studies indicate a higher reactivity of Pd overlays on noble metals with different kinds of adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous works have investigated the various 12 sorbents (pure metals [6,7], activated carbon [8-13], metal oxides [14,15] and metal 13 sulfides [16]), for the removal of mercury from coal-derived gas using experimental and 14 theoretical methods. It was found that transition metal sorbents show excellent adsorption 15 capacity for semi-volatile elements such as Hg [7,[17][18][19]. Density functional theory 16 (DFT) calculations for the mercury adsorption on metal (Ag, Au, Cu, Ni, Pt and Pd) 17 surfaces have found that the adsorption of Hg on Pd surface is stronger than on other 18 metal surfaces [17].…”
mentioning
confidence: 99%
“…14 On the basis of previous works, periodic DFT was used to investigate the adsorption of 15 Hg on the surfaces of M-substituted Pd(111) as well as PdM/γ-Al 2 O 3 (M = Au, Ag, Cu) to 16 explore the influence of the second metal on the Hg adsorption capacity of Pd sorbents. 17 The influences of Hg coverage (θ = 0.11 ~ 0.33 ML) on its adsorption over the 18 PdM/γ-Al 2 O 3 (M = Au, Ag, Cu) surfaces were also investigated. 19 20 The spin-polarized periodic density functional theory calculations were performed 21 using the Vienna Ab initio Simulation Package (VASP) [27,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation